1996
DOI: 10.1007/bf01797744
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal dysfunction in heart failure assessed by cardiac 123-iodine metaiodobenzylguanidine scintigraphy

Abstract: In patients with chronic heart failure, increased sympathetic activity and cardiac sympathetic neuronal dysfunction are present and have been related to unfavourable clinical outcome. Modification of these alterations with the objective to improve prognosis has become an important aim of pharmacological therapy for these patients. A noninvasive technique to assess sympathetic neuronal function at the cardiac level may be valuable in evaluating newly developed therapeutic strategies. 123-iodine metaiodobenzylgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The pathophysiological importance of the cardiac sympathetic nerve terminal NE uptake function is further supported by a recent study (55) of carvedilol in rats with dilated cardiomyopathy, in which the beneficial effects of carvedilol on cardiac function and myocardial fibrosis are associated with reduction of cardiac adrenergic neuronal damage as measured by [ 123 I]-metaiodobenzylguanidine (MIBG). Cardiac MIBG imaging has been used to assess cardiac sympathetic nerve terminal function in humans (52). These studies have shown that impaired cardiac adrenergic innervation as assessed by MIBG imaging is a valuable prognostic indicator, independent of left ventricular ejection fraction and circulating plasma NE, for increased mortality and morbidity in patients with chronic congestive heart failure (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological importance of the cardiac sympathetic nerve terminal NE uptake function is further supported by a recent study (55) of carvedilol in rats with dilated cardiomyopathy, in which the beneficial effects of carvedilol on cardiac function and myocardial fibrosis are associated with reduction of cardiac adrenergic neuronal damage as measured by [ 123 I]-metaiodobenzylguanidine (MIBG). Cardiac MIBG imaging has been used to assess cardiac sympathetic nerve terminal function in humans (52). These studies have shown that impaired cardiac adrenergic innervation as assessed by MIBG imaging is a valuable prognostic indicator, independent of left ventricular ejection fraction and circulating plasma NE, for increased mortality and morbidity in patients with chronic congestive heart failure (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac adrenergic nerve activity can be estimated using several techniques: first, using iodine‐123metaiodobenzylguanidine ( 123 I‐MIBG) as a noradrenaline analog 9 . 123 I‐MIBG is a guanethidine analog that shares the same uptake, storage, and release pathway as norephinephrine and has the potential to reflect the whole myocardial adrenergic pathway 9,10 . 123 I‐MIBG myocardial uptake indices can be used as a predictor of prognosis in patients with chronic HF 11–14 .…”
Section: Introductionmentioning
confidence: 99%